2014
DOI: 10.1128/iai.01237-13
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Toll-Like Receptor 2 in the Inflammatory Response and Major Histocompatibility Complex Class II Downregulation in Brucella abortus-Infected Alveolar Macrophages

Abstract: c Alveolar macrophages (AM) seem to constitute the main cellular target of inhaled brucellae. Here, we show that Brucella abortus invades and replicates in murine AM without inducing cytotoxicity. B. abortus infection induced a statistically significant increase of tumor necrosis factor alpha (TNF-␣), CXCL1 or keratinocyte chemoattractant (KC), interleukin-1␤ (IL-1␤), IL-6, and IL-12 in AM from C57BL/6 mice and BALB/c mice, but these responses were generally weaker and/or delayed compared to those elicited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 56 publications
(72 reference statements)
4
35
0
2
Order By: Relevance
“…Furthermore, during the late phase of control, only TNF-a deficiency strongly affected CFU counts of Brucella in the organs. In keeping with this observation, Brucella was recently shown to induce weak IL-1b, IL-6, and TNF-a production in lung alveolar macrophages compared with peritoneal macrophages (58). The chemokine receptor CCR2 has been implicated in the recruitment of inflammatory monocytes during infection (40).…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, during the late phase of control, only TNF-a deficiency strongly affected CFU counts of Brucella in the organs. In keeping with this observation, Brucella was recently shown to induce weak IL-1b, IL-6, and TNF-a production in lung alveolar macrophages compared with peritoneal macrophages (58). The chemokine receptor CCR2 has been implicated in the recruitment of inflammatory monocytes during infection (40).…”
Section: Discussionmentioning
confidence: 74%
“…The usual mouse model of B. abortus infection through an intraperitoneal route demonstrated that TLR2 does not contribute to host control of brucellosis in vivo [21]. However, TLR2 showed a role controlling B. abortus infection 1 wk after intratracheal infection [22]. In addition, our group demonstrated that TLR6 is required for full production of proinflammatory cytokines and MAPK activation in DCs, resulting in resistance to B. abortus infection [23].…”
Section: Introductionmentioning
confidence: 78%
“…Regarding resistance to B. abortus infection in mice, there is no consensus in the literature on the participation of TLR4, whereas TLR2 was reportedly to be not involved [18,49,53]. Even though possibly not involved in resistance to infection, it is well established that the recognition of B. abortus PAMPs by both TLR2 and TLR4 induce the secretion of TNF-␣, IL-12 and IL-6 by murine cells [18,42,[48][49][50][53][54][55]. Interestingly, TLR4-linked signaling interacting with Janus kinase 2 (TLR4-JAK2) is also involved in B. abortus internalization by murine macrophages [56].…”
Section: Cytokines Chemokines and Prrs/pampsmentioning
confidence: 96%